Screening, Vaccination, and Referrals as Viral Hepatitis Elimination Triad Among Internally Displaced Persons in Edo State, Nigeria. Issue 5 (10th December 2020) - Odimayo, Michael S.; Adebimpe, Wasiu O.; Jeff‐Agboola, Yemisi A.; Oyeyemi, Oyetunde T.; Okiei, Benedette N.; Adejumo, Oluwadamilola A.; Osungbemiro, Bamikole W.; Olajuyigbe, Ebenezer O.; Igbafe, Kate R.; Temitayo‐Oboh, Abiola O.; Faboya, Toyin; Oludiran, Moradeke Olubunmi; et al.
Abstract : Watch a video presentation of this article